CHALLENGES AND OPPORTUNITIES IN MUNICIPAL SOLID WASTE MANAGEMENT IN HISAR CITY OF HARYANA - Sonu Tak 1 , Dr. Manoj Kumar 2 (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This paper is an endeavor to offer an in-depth analysis of Municipal Solid Waste (MSW) management in Hisar City, Haryana, to identify strengths, weaknesses, opportunities, and threats (SWOT) within the existing system. Emphasizing the significance of effective waste management practices, it highlights achievements like source segregation and door-to-door collection. Despite the challenges of open dumping and lack of awareness, there is a significant opportunity to adopt advanced technologies and improve the current procedures. The per capita rate of MSW generation rate is .505 kg per day. The study aims to make recommendations for improving the municipal solid waste management procedures currently followed by the city corporations of Hisar. While the solid waste management system techniques that are now in place in the city need to be improved, there is a clear potential for improvement, instilling hope for a more efficient and environment-friendly town in Haryana.